فهم السياق القرآني لدى المفسرين بين التوجيه اللغوي والتذوق البلاغي - Abdul Ghani Bin Md Din; Omar bin Md Din; Ummu -Hani Abas; Ragab Ibrahim Ahmed Awad; Mohd Azizul Rahman Bin Zabidin (USIM Press, 2024)
VOL. 18 NO. 2